The Separation of National and Local Elections Examined from the Aspect of Election Implementation Effectiveness - Ashari, Ashari; Amalia, Riska Ari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The implementation of simultaneous elections or five (5) box elections has implications for the accumulation of workloads for election organizers, which within reasonable limits has an impact on the quality of general election implementation. In addition to the threat to the quality of general election implementation, the accumulation of workloads for organizers concentrated in a certain time period due to the tight timing of general elections in the same year causes relatively long periods of free time for election organizers. The purpose of this study is to determine the implications of the separation of national and local elections and its effectiveness in the implementation of elections in Indonesia. This research is a type of normative legal research that uses a legislative approach. The results explain that the separation of national and local elections in the implementation of elections has implications for regulatory changes related to election laws and regional elections that are not only related to technical aspects, but also touch on the institutional design of election organizers, the flow of stages of implementation, nomination mechanisms, and budget management of encouraging rationality of voters in using their voting rights, the transfer of government power at the central and regional levels which is mutually consolidated and will reduce the coattail effect between presidential and regional legislative elections. Furthermore, separating national and local elections will ensure greater election effectiveness, as voters face simpler choices. Logistics provision and distribution will be faster and more accurate, and local figures will be more likely to dominate the House of Representatives (DPR) ticket.